ORGANIZATIONAL CHALLENGES FACING INTEGRATING E-GOVERNMENT SYSTEMS: AN EMPIRICAL STUDY - Al-Sebie, Madi (European Scientific Journal, ESJ, 2014)
Through passing of e-government systems into different stages, theintegration stage of e-government can be considered the most important oneof the implementation of an e-government system. It represents the highestpotential of providing customers (citizens, businesses and publicadministration) with full online interaction with their governments thusenabling them to obtain government information and services from a singlepoint of access. The importance of the integration stage of an e-governmentsystem and its highest positive impact motivate local/national governmentsto reach this stage.However, in order to reach the integration stage of e-government,local/national governments face various challenges; these challenges couldbe political, technical, economic, social or organizational. In fact, there is alack of studies focusing on identifying the importance, categorization andpresentation of strategies for overcoming organizational challenges.Therefore, this paper will try to fill the information gap based on empiricalcase studies of two local governments. This article will identify theimportance, categorization, and presentation of the strategies for overcomingorganizational challenges facing an integration e-government system.